ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-V/2007 TENTANG MEKANISME PEMBENTUKAN PENGADILAN AD HOC DALAM PELANGGARAN HAM DI INDONESIA - Muhammad Roziki (Fakultas Hukum Universitas Islam Malang, 2020)
ABSTRACTLaw Number 26 of 2000 concerning Human Rights Courts. This regulation is responsive, considering that there have been many past gross human rights violations involving state institutions. However, there are legal problems when in Article 43 Paragraph (2) of the Human Rights Court Law which explains that a Human Rights Court is formed on the basis of